Delayed HIV diagnosis in a cystic fibrosis patient: Not just another exacerbation - Sapna Bhatia (Elsevier, 2021)
Patients with cystic fibrosis (CF) are living longer due to advancements in treatment. We present a patient with CF in whom diagnoses of Human Immunodeficiency Virus (HIV) and severe pneumocystis pneumonia were delayed due to anchor bias. Our case highlights the importance of routine age-appropriate health screenings in patients with CF. In addition, we discuss the number of management challenges that may arise in patients with a dual diagnosis of CF and HIV.